Amyloid Formation by Globular Proteins: The Need to Narrow the Gap Between in Vitro and in Vivo Mechanisms - Faravelli, Giulia; Mondani, Valentina; Mangione, P. Patrizia; Raimondi, Sara; Marchese, Loredana; Lavatelli, Francesca; Stoppini, Monica; Corazza, Alessandra; Canetti, Diana; Verona, Guglielmo; Obici, Laura; Taylor, Graham W.; et al. (Frontiers in Molecular Biosciences, 2022)
The globular to fibrillar transition of proteins represents a key pathogenic event in the development of amyloid diseases. Although systemic amyloidoses share the common characteristic of amyloid deposition in the extracellular matrix, they are clinically heterogeneous as the affected organs may vary. The observation that precursors of amyloid fibrils derived from circulating globular plasma proteins led to huge efforts in trying to elucidate the structural events determining the protein metamorphosis from their globular to fibrillar state. Whereas the process of metamorphosis has inspired poets and writers from Ovid to Kafka, protein metamorphism is a more recent concept. It is an ideal metaphor in biochemistry for studying the protein folding paradigm and investigating determinants of folding dynamics. Although we have learned how to transform both normal and pathogenic globular proteins into fibrillar polymers in vitro, the events occurring in vivo, are far more complex and yet to be explained. A major gap still exists between in vivo and in vitro models of fibrillogenesis as the biological complexity of the disease in living organisms cannot be reproduced at the same extent in the test tube. Reviewing the major scientific attempts to monitor the amyloidogenic metamorphosis of globular proteins in systems of increasing complexity, from cell culture to human tissues, may help to bridge the gap between the experimental models and the actual pathological events in patients.